Developing English for Sustainable Tourism: A Needs Analysis of Eco-Tourism Practitioners - Suparlan, Suparlan; Rizal , Samsul (Journal of Advance in Language, Literature, and Education, 2025)
Sustainable tourism has gained significant attention as an approach to balancing environmental conservation, economic growth, and cultural preservation. However, eco-tourism practitioners often face challenges in effectively communicating with international tourists due to limited English proficiency tailored to their specific needs. This study aims to analyze the English language needs of eco-tourism practitioners and develop an English for Specific Purposes (ESP) syllabus that aligns with the requirements of sustainable tourism. Employing a mixed-methods approach, data were collected through surveys, interviews, and field observations involving eco-tour guides, local community members, and tourism stakeholders. The findings indicate that eco-tourism practitioners require English proficiency in key areas such as environmental interpretation, cultural storytelling, customer service, and crisis communication. Furthermore, the study highlights the gap between existing general English training and the practical linguistic demands of eco-tourism. Based on the needs analysis, a tailored ESP framework is proposed, incorporating communicative tasks, contextual vocabulary, and interactive learning strategies. The study underscores the importance of designing language programs that not only enhance professional communication skills but also promote sustainability awareness. The findings contribute to ESP curriculum development and offer insights for policymakers and educators in integrating sustainable tourism into language training programs.